Dividend-Protected Convertible Bonds and the Disappearance - Bruce D. Grundy; Patrick Verwijmeren (Tinbergen Institute, 2012)
Firms have not historically called their convertible bonds as soon as they could force conversion. Various explanations for the delay rely on the size of the dividends that bondholders forgo so long as they do not convert. We investigate an important change in convertible security design, namely that more than 95 percent of recent convertible bond issues are dividend-protected. Dividend protection means that the conversion value of the shares into which a bond is convertible is unaffected by dividend payments and dividendrelated rationales for call delay become moot. We document that dividend-protectedconvertibles are called as soon as conversion can be forced.
urn:NBN:nl:ui:31-1871/38467
Keywords: G2; G32; 330; Call policy; Dividend protection; Convertible securities; Security design; Wandelanleihe; Dividende; Unternehmensfinanzierung; Welt